Network Coding (IntechOpen, 2023)
Network coding is an elegant and novel technique that allows nodes in the network to perform coding operations at the packet level. In particular, network coding represents a powerful approach to protect data from losses due to link disconnections and can also exploit the combination of multiple links to deliver data to users with the possibility of recoding at intermediate nodes. This phenomenon will reduce information congestion at some nodes or links, which will improve the network information flow such as to increase network throughput and robustness. This book is intended to provide the current R&D trends in coding, detection, and signal processing applied to communications in wireless and wired networks.